2007
DOI: 10.1007/s10342-007-0187-1
|View full text |Cite
|
Sign up to set email alerts
|

A population genetic study in a scattered forest species, wild service tree [Sorbus torminalis (L.) Crantz], using RAPD markers

Abstract: Wild service tree [Sorbus torminalis (L.) Crantz] is a forest tree widespread in Europe, characterized by a scattered distribution. Its hermaphroditic flowers are pollinated by insects, and outcrossing is the prominent mating system, also due to the presence of gametophytic self-incompatibility. Genetic diversity and differentiation of 22 populations from northwestern Italy were investigated by means of variation scored at 53 polymorphic RAPD (Random Amplified Polymorphic DNA) loci. Populations differed in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
1
16
0
3
Order By: Relevance
“…In other European countries, the tree is considered a rare woody plant with small, isolated populations , Rasmussen and Kollmann 2004b, Oddou-Muratorio et al 2005, Belletti et al 2008, Kausch-Blecken von Schmeling 1994, Roper 1993, Bednorz et al 2006, Paganová 2008, Demesure et al 2000. This species was originally scattered in the natural landscape, but traditional human forest management since medieval times has favoured light-demanding forest species (Wohlgemuth et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other European countries, the tree is considered a rare woody plant with small, isolated populations , Rasmussen and Kollmann 2004b, Oddou-Muratorio et al 2005, Belletti et al 2008, Kausch-Blecken von Schmeling 1994, Roper 1993, Bednorz et al 2006, Paganová 2008, Demesure et al 2000. This species was originally scattered in the natural landscape, but traditional human forest management since medieval times has favoured light-demanding forest species (Wohlgemuth et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Its distribution and altitude dependence differ in various parts of Europe. Although the altitudinal limit in Britain is 300 m (Roper 1993), Belletti et al (2008) reported the wild service tree at 100-1000 m a.s.l. in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, only few stems over 185 individuals were found to be the result of vegetative reproduction in a French population of S. torminalis . Some studies may underreport the natural incidence of clonality because they were specifically designed to avoid sampling from the same genets, which prevented precise estimation of the extent of clonality (Belletti et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies report on the genetic diversity of S. torminalis populations throughout Europe (Demesure et al 2000, Oddou-Muratorio et al 2001a, Hoebee et al 2006, Angelone et al 2007, Belletti et al 2007, studies focusing on peripheral populations of the species are scarce (Rasmussen & Kollmann 2007b). The latter authors found that small populations located at the northern limits were characterized by high clonality and low genetic variation (Rasmussen & Kollmann 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Demography is the main factor influencing genetic histories; nevertheless, neutral markers may present stochasticity in a given demographic context that is modulated by non-stochastic forces such as selection. The influence of the above factors in shaping extant population genetic diversity and structure is of paramount importance in order to secure the adaptive potential of populations and to formulate appropriate management and conservation strategies for sustainability (Tessier du Cros et al 1999;Boshier and Amaral 2004;Belletti et al 2008).…”
Section: Introductionmentioning
confidence: 99%